Demonstration of the Medial Subvastus Knee Exposure for MACI Implantation - Deryk G. Jones MD, FAAOS, FAOA; Jordan M. Grilliot DO (SAGE Publishing, 2023)
Background: There are several techniques for knee exposure in treating chondral defects with restorative procedures. The medial subvastus knee exposure is often overlooked when choosing the surgical approach. When properly performed, the medial subvastus approach can allow for the treatment of a wide range of pathology while preserving the extensor mechanism. Indications: We present a case of an active 40-year-old man with persistent left knee pain noted to have a full-thickness medial femoral condylar articular cartilage defect in an otherwise healthy appearing knee. Technique Description: The rationale and considerations for the medial subvastus knee exposure in treating a chondral defect with an autologous chondrocyte implant are discussed. Careful consideration of the approach, intra-articular exposure, and closure are emphasized to achieve optimal outcomes. Results: At 18 months postoperative, the patient reported no knee pain with improvements made in Knee injury and Osteoarthritis Outcome Score (KOOS), Lysholm, and International Knee Documentation Committee (IKDC) scores. These results are consistent with our institutions larger cohort of 26 patients undergoing matrix-induced autologous chondrocyte implantation (MACI) using the subvastus approach. These improvements in patient-reported outcomes are maintained at 2 years postoperative and are consistent with other published outcomes of the MACI procedure. Discussion/Conclusion: Excellent results in addressing chondral pathology about the knee can be achieved by selecting the appropriate surgical access. The subvastus approach has several advantages such as preserving the quadriceps mechanism, improving postoperative quadriceps muscle strength, conservation of the patellar genicular blood supply and possibly reducing postoperative pain that can result in a faster rehabilitation. When performed systematically and carefully, complete exposure of the knee can be achieved to facilitate a wide variety of surgical interventions. In patients undergoing cartilage restoration procedures, the medial subvastus approach should be considered in the surgeon's armamentarium. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.